KRAS mutation as a prognostic factor and predictive factor in advanced/metastatic non-small cell lung cancer: A systematic literature review and meta-analysis. (2020) - Goulding, Rebecca Ellen; Chenoweth, Matthew; Carter, Gebra Cuyun; Boye, Mark Ernest; Sheffield, Kristin M; John, William J; Leusch, Mark Steven; Muehlenbein, Catherine Elizabeth; Li, Li; Jen, Min-Hua; Rojubally, Adina; Jansen, Jeroen; et al.
Highlights: KRAS is a negative prognostic factor for survival and response in advanced/metastatic NSCLC. KRAS may be associated with poor prognosis for survival and response in advanced/metastatic NSCLC. More published evidence is needed on KRAS as an treatment effect modifier. Abstract: KRAS (Kirsten Rat Sarcoma) is the most common oncogenic mutation detected in patients with non-small cell lung cancer (NSCLC). However, the role of KRAS as either a prognostic factor or predictive factor (modifier of treatment effects) in NSCLC is not well established at this time. This systematic literature review (SLR) and meta-analysis synthesized the available evidence regarding the role of KRAS mutation as a predictive factor and/or prognostic factor of survival and response outcomes in patients with advanced/metastatic (stage IIIB-IV) NSCLC. Relevant clinical trials and observational studies were identified by searching MEDLINE, Embase and Cochrane Register of Controlled Trials. Meta-analyses were performed using data extracted from multivariable and univariable analyses from clinical studies to assess the empirical evidence of KRAS mutation status as a prognostic or/and predicitive factor. 43 selected studies were identified by the SLR and included in this meta-analysis. Pairwise meta-analyses of hazard ratios (HRs) reported in randomized controlled trials (RCTs) did not demonstrate a significant prognostic effect of mutant KRAS on overall survival (OS) (HR=1.10; 95% CI [0.88, 1.38]) or progression free survival (PFS) (HR=1.03; 95% CI [0.80, 1.33]). However, when conducting meta-analyses on HRs reported in observational studies, a statistically significant negative prognostic effect of mutant KRAS was observed (OS HR=1.71; 95% CI [1.07, 2.84]; PFS HR=1.18; 95% CI [1.02, 1.36]). Meta-analyses of objective response rate (ORR) in RCTs demonstrated a negative prognostic effect of mutant KRAS (RR=0.38; 95% CI [0.16, 0.63]). Limited data were available to evaluate the role of KRAS mutation as a predictive factor. In conclusion, this research offers evidence that KRAS mutation may be a negative prognostic factor for survival and response outcomes in patients with advanced/metastatic NSCLC, but further research is needed to address conflicting results on the importance of KRAS mutations as a predictive factor.